Exploring Malay Culture in Madrasah Learning: Revealing the Value of Malayness in Madrasah Tsanawiyah Curriculum - Syahraini Tambak; Muhammad Ali Noer; M. Yusuf Ahmad; Daharmi Astuti; Najmi Hayati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
Research on Malay culture has been carried out a lot, but seeing it in its application in the madrasah Tsanawiyah curriculum has not yet been found. This study aims to determine the implementation of Malay culture as a vision of Riau 2020 in the 'Madrasah Tsanawiyah' educational curriculum in Riau Province. This research is a descriptive study that describes the implementation of the Riau Malay culture in the educational curriculum in all Madrasah Tsanawiyah in Riau Province. This research was conducted at Madrasah Tsanawiyah in 12 districts/cities in Riau Province, involving 24 heads of Madrasah Tsanawiyah. The data collection technique used was a questionnaire and the data were analyzed descriptively. The results showed that 39% of the Riau Malay culture in the Madrasah Tsanawiyah education curriculum in Riau Province was accommodated and implemented in the curriculum. The application of Malay culture is very urgent to be disseminated in the Madrasah Tsanawiyah curriculum in Riau Province, by the Education Office and the Regional Office of the Ministry of Religion of Riau Province to develop this local wisdom in the community.